Comparison of music and vapocoolant spray in reducing the pain of venous cannulation in children age 6-12: a randomized clinical trial - Masoomeh Ghasemi; Poria Hoseinialiabadi; Fatemeh Yazdanpanah; Maryam Askaryzadeh Mahani; Leila Malekyan; Kazem Najafi; Mohammadreza Arab; Mansour Arab; Hadi Ranjbar (BMC, 2022)
Abstract Background Venous cannulation is among the most stressful and painful experiences of children hospitalization. Children with thalassemia need regular blood transfusion which needs venous access each time. The quality of care and quality of life of children will be improved if appropriate methods are used to reduce pain. This study aimed to compare vapocoolant spray and music in the reduction of pain of Venous cannulation in children with thalassemia. Methods The study was a randomized controlled clinical trial with a cross-over design. Thirty-six children with thalassemia from Thalassemia Patients of Pasteur Hospital in Bam from October to December 2020 and were recruited and randomly allocated to two arms. The pain of venous cannulation (no treatment) was measured in the first blood transfusion session as control. In the second and third sessions, two arms received music and vapocoolant spray before the venous cannulation with a cross-over design. The intensity of pain was measured by a Visual Analogue Scale (VAS). The change in pain scores was tested by ANOVA and Tukey post-hoc test between three measurements. Results During and after the cannulation, the pain was significantly lower in the vapocoolant measurement than in control and music (p < 0.05). There was a significant effect of vapocoolant spray during the procedure F (2, 90) = 25.604, p = 0.001. Also, there was a significant effect of vapocoolant spray after the procedure F (2, 90) = 10.087, p = 0.004). Music did not reduce the pain during cannulation (p = 0.413) and after that (p = 0.807) significantly when compared with control. Conclusions Vapocoolant was an effective method of pain reduction in the reduction of venous cannulation pain. Music was not effective in the reduction of venous cannulation pain when we compared it with controls. The pain of venous cannulation is rated as high and it can have negative effects on the children. There is a need to do more research on the methods of pain reduction of venous cannulation. Trial registration The trial is registered: IRCT20111019007844N13, 13/03/2020. Available at: https://en.irct.ir/trial/42904 .